ANALISA FAKTOR-FAKTOR YANG MENYEBABKAN KESALAHAN PENGIRIMAN BARANG DARI GUDANG (STUDI KASUS: PT. NIRO CERAMIC SALES INDONESIA) - Donny Hendrawan (MIX: JURNAL ILMIAH MANAJEMEN, 2013)
Abstract: This thesis proposes to analyze some factors that caused error in delivery endproducts from the warehouse to customer at PT. Niro Ceramic Sales Indonesia. Thisresearch use the Five Whys Analysis and Fishbone Analysis as tools to identify somefactors that caused errors in delivery end products from the warehouse. Results of thisresearch showed that error of shipments of end products from warehouse to customer arecaused by humans (the employee do not have enough training and do not have enoughworking hours) and methods (lack of Standart Operating Procedure, no exception ruleorder for loyal customers and the material order request always urgently needed), evenfor media or environment factors are not enough lighting and indoor building conditionsis not properly manage. Based on that result, this research proposes some recomendationfor the management of the company, i. e. conduct a routine training for all warehousepersonnel, add the number of warehouse personnel, change the working hours becometwo shifts per day and evaluate daily expenditures‟s procedure for delivery of endproduct from warehouse to the customer or to dealer.Keywords: Error Delivery, Five Whys Analysis, Fishbone Analysis